(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The article examines the use of online platforms and the possibilities they offer for supplementary and complementary learning. Some commonly used platforms among learners are presented and various studies have been conducted. The results were analyzed and a comparative assessment was made for the effectiveness of digital platforms in learning through described results of real tests. An increase in the knowledge of learners when using online platforms has been reported.